How I Do It: Percutaneous Image-guided Peritoneal Dialysis Catheter Insertion - Mohammad Arabi; Sultan Alammari; Shahbaz Qazi; Omar Bashir; Refaat Salman; Yousof Alzahrani; Elwaleed Elhassan; Mohammad Almoaiqel (The Arab Journal of Interventional Radiology)
Peritoneal Dialysis (PD) catheter insertion is traditionally performed using open surgical or laparoscopic techniques. The minimally invasive percutaneous PD catheter insertion techniques guided by fluoroscopy and ultrasound proved to provide comparable results in terms of catheter survival and dysfunction rates and lower incidence of catheter related peritonitis and leak. Percutaneous insertion by interventional radiologists offers more flexible scheduling and efficiency compared to surgical approaches that require operating room booking and general anesthesia. Here we report a step-by-step guide for percutaneous image-guided PD catheter insertion based on our institutional experience and previous best practice recommendations in the literature.